Advertising the Uneasy Persuasion. - Schudson, Michael (Taylor & Francis, 2013)
What does advertising do? Is it the faith of a secular society? If so, why does it inspire so little devotion? Advertising, the Uneasy Persuasion is a clear-eyed account of advertising as both business and social institution. Instead of fuelling the moral indignation surrounding the industry, or feeding fantasies of powerful manipulators, Michael Schudson presents a clear assessment of advertising in its wider sociological and historical framework, persuasively concluding that advertising is not nearly as important, effective, or scientifically founded as either its advocates o.